H2O2-Scavenging Activity and Hyaluronidase Inhibition Scutellarin and Apigenin in Basil Leaf Extract - Yusuf, Lydia; Girsang, Ermi; Nasution, Ali Napiah; Elvira, Cut; Wibowo, Satrio Haryo Benowo; Widowati, Wahyu (Fakultas Kedokteran Universitas Brawijaya, 2021)
The potential utilization of flavonoid compounds, especially scutellarin, and apigenin, contained in basil (Ocimum basilicum L.) leaf extract to manage the aging effects on the skin, that occurs because of over-activated hyaluronidase enzyme and oxidative stress due to hydrogen peroxide (H2O2) radicals, is not well known. This study was conducted to assess the H2O2 scavenging activity and the inhibition of hyaluronidase from scutellarin and apigenin at various concentrations. The study was conducted by measuring H2O2 scavenging inhibition and hyaluronidase inhibition of scutellarin and apigenin in various concentrations using the spectrophotometry method. The various activity was tested using the One-Way ANOVA test followed by Tukey post hoc test. IC50 values were calculated based on linear regression equations of H2O2 scavenging inhibition and hyaluronidase inhibition. The analysis showed the highest H2O2 scavenging activity was found in scutellarin with IC50 158.76 Î¼g/mL. Scutellarin has greater scavenging activity than apigenin. Hyaluronidase inhibition of scutellarin with IC50 35.25 Âµg/mL, while apigenin was 162.86 Âµg/mL. Scutellarin has higher hyaluronidase inhibition activity than apigenin. Antioxidant and antiaging effects of basil leaf extract caused by phytochemical compounds contained, especially scutellarin.